THE SIGNALS IMMUNITY OF THE IMPROVED MODULATION BY CYCLIC SHIFT WITH ADAPTATION TO INFORMATION TRANSFER RATE IN MULTIMODE PROPAGATION ENVIRONMENT - Artem O. Moskalenko; Serhii V. Voloshko; Ihor I. Sliusar; Ihor Y. Rubcov (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The results of comparative analysis of broadband modulation perspective methods are in presented. Basic principles of perspective radiointerfaces construction are considered. It is set as a result, that desirable property of signals modulation methods that are candidates on the use in perspective radiointerfaces, is possibility of adaptation to the terms of radio waves distribution. The method of adaptive modulation is considered by the cyclic code shift keying with possibility of information transfer speed change. The model of discrete communication channel is presented for research of the noise immunity of improved CCSK- modulation signals in the conditions of multipath waves propagation. The noise immunity of improved CCSK- modulation signals in the conditions of multipath waves propagation is investigational.